Investigating the Motivation of Adventure Park Visitors - Boda, Eszter; Bácsné Bába, Éva; Müller, Anetta (International Journal of Engineering and Management Sciences, 2018)
In the world of runaway, “homo-sitting” and mobile telephones, the quality of leisure time is gaining increasing importance, most of which is the experience gained and the characteristics of existing natural factors. A variety of thematic and adventure parks are reported every year, increasing travel and visitors' growth every year, the service offering of which broadly satisfies the needs of modern man and kind. In the focus of our research, we set the link between recreational habits and motivation of adventure park visiting. Use the survey questionnaire to calibrate consumer habits (n = 408). There were significant differences in the number of factors studied, such as those who seek more physical activities in their free time and prefer to respond to the challenge and extravagance motivating motivation in each of the adventure parks, or even for leisure-time enthusiasts. Our research reveals that service providers should consider targeting their leisure time habits, for example, they can benefit from a thorough consumer mapping from the point of view of electoral motivation.